Postoperative Recovery in the Youngest: Beyond Technology - Carina Sjöberg; Mona Ringdal; Pether Jildenstål (MDPI AG, 2024)
Background: Measuring and interpreting vital signs in pediatric patients recovering from anaesthesia, particularly those up to 36 months old, is challenging. Nurses' decision-making regarding the level of monitoring must balance patient safety with individualized care. This study aimed to explore the perceptions of critical care nurses and registered nurse anesthetists regarding their experiences and actions when making decisions about vital sign monitoring for children in post-anesthesia care units (PACUs). Methods: A qualitative study utilizing the critical incident technique was conducted. Interviews were performed with a purposeful sample of 17 critical care nurses and registered nurse anaesthetists from two hospitals. Results: Nurses reported that the rationale for decisions concerning the need for vital sign monitoring in children was both adequate and inadequate. Actions were taken to adjust the monitoring of vital signs, optimizing conditions for assessment and ensuring the child's safe recovery. Conclusions: The complexity of accurately monitoring children makes it challenging for nurses in the PACU to adhere to guidelines. Evidence-based care and safety are compromised when technology has limitations and is not adapted for paediatric use, leading to a greater reliance on experience and clinical assessment. This reliance on experience is crucial for reliable assessment but also entails accepting greater risks.